2014
DOI: 10.4303/ajpm/235871
|View full text |Cite
|
Sign up to set email alerts
|

Positive Tumor Margins in Wide Local Excision of Breast Cancer: A 10-Year Retrospective Study

Abstract: Background. The safety of wide local excision as a standard surgical option for early stage breast cancer management in Ghana has not been evaluated. The aim of this study was to use retrospective histopathological descriptive study to evaluate the prevalence of positive tumor margins in wide local excision specimens and offer recommendations. Study design. We reviewed 147 breast lumps, following wide local excision, which were received in the Department of Pathology, for positive tumor margins. The data was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 33 publications
3
8
1
Order By: Relevance
“…Nodal involvement by malignant tumour and the presence of positive tumour margins are indicators of systemic disease, recurrence after surgery and treatment failure. [21][22][23] The immunohistochemical profile of this case is in keeping with a previous study conducted at the Korle-Bu teaching Accra Ghana on MBCs. [9,24] The breast cancer by pathological staging was of a high stage (pT4bN1M), in keeping with reports on male breast cancer.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nodal involvement by malignant tumour and the presence of positive tumour margins are indicators of systemic disease, recurrence after surgery and treatment failure. [21][22][23] The immunohistochemical profile of this case is in keeping with a previous study conducted at the Korle-Bu teaching Accra Ghana on MBCs. [9,24] The breast cancer by pathological staging was of a high stage (pT4bN1M), in keeping with reports on male breast cancer.…”
Section: Discussionsupporting
confidence: 77%
“…[27] Our patient has most of these poor prognostic indicators. [22][23][24][25][26][27][28] For instance, he was 79-years with large tumour size, skin ulceration, fixation to the anterior chest wall with high pathological stage at diagnosis and hence the poor outcome (death) in this case.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 However, the rate varies globally based on the study types and methods. 14,46 In this current study conducted in the northern part of Ghana, the prevalence of positive tumour margins in large samples was 35.2%.This rate is much higher than what was reported in previous studies in Ghana. 14,46 For instance, Der et al, 46 in Accra Ghana reported a rate of 21.1% in wide local excision specimens.…”
Section: Discussioncontrasting
confidence: 50%
“…This is similar to what Der et al documented in Ghana (4:1) and t Seyoum et al documented in Ethiopia (4.1:1) respectively. 37,43 It has been richly documented in the literature that thyroid cancers is commoner among females. 37,44−47 According to Rahbari et al, it is only the differentiated thyroid cancer that is commoner in females with the poorly differentiated subtype having equal gender distribution.…”
Section: Discussionmentioning
confidence: 99%